2011
DOI: 10.1063/1.3527067
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of carbon adatoms to graphene and its nanoribbons

Abstract: Adsorption and diffusion of 3d transition metal atoms on the GaN (0001) This paper investigates the adsorption of carbon adatoms on graphene and its nanoribbons using first-principles plane wave calculations within density functional theory. The stability at high carbon adatom coverage, migration, and cluster formation of carbon atoms are analyzed. Carbon adatoms give rise to important changes in electronic and magnetic properties even at low coverage. While bare graphene is nonmagnetic semimetal, it is metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 31 publications
1
64
1
Order By: Relevance
“…The dumbbell (DB) structure [20][21][22][23] of silicene has been the most critical ingredient in the construction of the layered bulk phase of Si. A single Si adatom initially at the top site of silicene pushes down the parent Si atom underneath to arrange a DB [22] structure as shown in Fig.…”
Section: Dumbbell Silicenementioning
confidence: 99%
“…The dumbbell (DB) structure [20][21][22][23] of silicene has been the most critical ingredient in the construction of the layered bulk phase of Si. A single Si adatom initially at the top site of silicene pushes down the parent Si atom underneath to arrange a DB [22] structure as shown in Fig.…”
Section: Dumbbell Silicenementioning
confidence: 99%
“…Unusual properties of graphene promising for a variety of novel applications [23][24][25][26][27][28] have also triggered significant interest in one or several atom-thick honeycomb structures of binary compounds. Early experimental studies aiming to synthesize and characterize novel monolayer materials have revealed that graphene-like sheets of BN are also stable.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen functionalization creates new band gap openings in graphene [10], and carbon adatoms significantly modify the electronic and magnetic properties of graphene [11][12][13].…”
Section: Introductionmentioning
confidence: 99%